Current trend of colonic diverticulosis in patients undergoing colonoscopy in a tertiary care hospital in Northern India - Shiekh, Shabir Ahmad; Kawoosa, Zafar Iqbal; Lone, Shafat Sideeq; Wani, Irfan Rasool; Shah, Asif Iqbal; Wani, Zafar Ali; Khan, Bilal Ahmad; Zargar, Showkat Ali (Asian Journal of Medical Sciences, 2021)
Background: Diverticular disease of the colon has a wide geographic variation and is a very common cause of hospital visits and admissions in the west. Contrary to this there is scarce data on colonoscopic prevalence of diverticular disease from our country. Aims and Objectives: To determine the prevalence of colonic diverticulosis and concomitant colonoscopic pathologies among patients undergoing colonoscopy in a tertiary care gastrointestinal endoscopy setting in Northern India. Materials and Methods: All adult patients who underwent colonoscopy for various indications and were diagnosed to have colonic diverticulosis from August 2016 to December 2019 in the Department of Gastroenterology, Shifa Medical centre, Srinagar, Kashmir, India were included in the study. Results: Out of a total of 4500 colonoscopic procedures, diverticulosis was seen in 190 cases with an overall prevalence of 4.2%. Fifty-six percent of these were males and 44% were females. In 77 (40.52%) patients diverticulosis was seen in left colon, in 72 (37.89 %) in right colon and in 41 (21.57 %) diverticulosis was noted in pancolonic distribution. Adenomatous polyps were seen in 27 % of the cases. Conclusion: Colonic diverticulosis has very low prevalence in this northern Indian state. Adenomatous polyps are commonly associated with this condition.